2004
DOI: 10.1200/jco.2004.06.078
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Quality of Life in Routine Oncology Practice Improves Communication and Patient Well-Being: A Randomized Controlled Trial

Abstract: Routine assessment of cancer patients' HRQL had an impact on physician-patient communication and resulted in benefits for some patients, who had better HRQL and emotional functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
1,012
6
18

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,188 publications
(1,079 citation statements)
references
References 28 publications
(4 reference statements)
29
1,012
6
18
Order By: Relevance
“…Among woman who expressed high initial psychological needs, those who received the intervention experienced a greater reduction in psychological needs compared with those who did not receive the intervention. This finding reinforces the importance of assessing individual needs and providing this information to the treatment team for intervention, in line with Velikova et al (2004) earlier work. It also reflects earlier findings (McArdle et al, 1996) that showed that empathy combined with information reduced psychological distress in women with breast cancer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Among woman who expressed high initial psychological needs, those who received the intervention experienced a greater reduction in psychological needs compared with those who did not receive the intervention. This finding reinforces the importance of assessing individual needs and providing this information to the treatment team for intervention, in line with Velikova et al (2004) earlier work. It also reflects earlier findings (McArdle et al, 1996) that showed that empathy combined with information reduced psychological distress in women with breast cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Very few trials have investigated brief interventions, and those that have tended not to produce significant change, probably due to the lack of systematic individual tailoring (Newell et al, 2002). One exception was a study by Velikova et al (2004). This study showed that systematically assessing patients' quality of life and providing this information to the treating doctor improved patient quality of life and emotional functioning.…”
Section: The Present Studymentioning
confidence: 97%
“…relaxation techniques, developmentally appropriate distraction) are highly effective in reducing pain and anticipatory fear (Duff 2003). It has been shown in other chronic paediatric diseases that addressing social issues and emotional distress during regular hospital follow-ups is supportive and that the use of HrQoL questionnaires (Santana and Feeny 2013) significantly increases meaningful patient-physician communication and patient well-being (Velikova et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was felt that patient-reported adverse event information should be incorporated into published study results and drug labels. These findings reflect an overall movement in clinical research and drug regulatory policy towards favoring patient self-reports for those experiences best known to the patient, such as symptoms [3][4][5][13][14][15][16][17][18]. Of particular note is the FDA's recent guidance for industry on patient-reported outcomes measures in medical product development to support labeling claims, in which patient-reported outcomes (PROs) are advocated for measuring subjective experiences of patients related both to treatment benefit and risk [12,19].…”
Section: Discussionmentioning
confidence: 94%